Can Secondary Information Inform About Population Trends of Carnivores In Borneo? - Mohd-Azlan, J.; Belant, Jerrold L.; Meijaard, E. (National University of Singapore, 2013)
Effective methods for estimating occurrence and abundance of carnivores are limited and often expensive in labour or equipment. Conducting interviews about wildlife species, including carnivores,is a common tool used in Borneo and throughout Southeast Asia to investigate species distribution and understand their conservation status. Such surveys are appealing because of perceived savings in time and equipment; however, biases in amount of available information, miscommunications about species of interest, and species misidentifi cation can result in errors of unknown magnitude, rendering results of at least some surveys suspect. Hence, it becomes diffi cult to disentangle accurate from inaccurate information. Studies are needed to investigate the variation in effectiveness of interview surveys. Also better guidance is needed to clarify under which conditions secondary surveys can be used with confi dence, and for which particular audience. Until the factors that bias results are identifi ed and, where possible, accounted for, the main use of secondary surveys for carnivores and other diffi cult to identify or rarely encountered species will be to help develop a dialogue between people that reside or work in conservation project areas and the investigators working on such projects. Secondary surveys may also serve as a tool to help identify hypotheses to be addressed in studies with strong experimental designs.